The Giza 'written' landscape and the double project of King Khufu. (2nd January 2016) - Magli, Giulio
ABSTRACT: In recent years, different scientific disciplines – from physics to Egyptology, from geology to archaeoastronomy – have generated a series of clues pointing to the possibility that the original project of the pyramid complex of Khufu at Giza also included the project of the second pyramid complex at the same site, that of Khafra. The aim of the present paper is to discuss this issue in a systematic fashion and to explore its implications in terms of the way the ancient Egyptians conceived and built monuments and sacred landscapes during the fourth dynasty.